1997
DOI: 10.1029/97ja01649
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of the high‐degree multipoles of Neptune's magnetic field: An Euler potentials approach

Abstract: Abstract. A new technique of calculating the Euler potentials a and/3 based on the geometrical relations between the magnetic field structure and Euler potentials [Huang and Yu, 1995] was used to determine the a and/3 coordinates of Neptune's magnetic field. The result is a mathematical definable coordinate system for a field of which the nondipole terms are nonnegligible. A framework is thus established for future studying of plasma dynamics such as particle drifts and plasma convection. The magnetic field mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…This particular choice is made in reference to BoÈ strom (1975), Peymirat and Fontaine (1994b) and Stern (1994b) who showed that the derivation of the magnetospheric plasma transport equations is simpli®ed if a 1 is function of 5 only. Ho et al (1997) with h pa2 and hence dh = 0. Along a curve of constant value of a 1 on ,…”
Section: Derivation Of a ®Rst Set Of Euler Potentialsmentioning
confidence: 99%
See 3 more Smart Citations
“…This particular choice is made in reference to BoÈ strom (1975), Peymirat and Fontaine (1994b) and Stern (1994b) who showed that the derivation of the magnetospheric plasma transport equations is simpli®ed if a 1 is function of 5 only. Ho et al (1997) with h pa2 and hence dh = 0. Along a curve of constant value of a 1 on ,…”
Section: Derivation Of a ®Rst Set Of Euler Potentialsmentioning
confidence: 99%
“…Equation (16) would be equivalent to the relationship used by Ho et al (1997) if the unit area were the elementary area in the (r, h, u) space. a 1 (5) is de®ned similarly to the dipole approximation as…”
Section: Derivation Of a ®Rst Set Of Euler Potentialsmentioning
confidence: 99%
See 2 more Smart Citations
“…To find Euler potentials for more complex fields, e.g., magnetospheric models, various numerical methods have been developed [Ho et al, 1997;Peymirat and Fontaine, 1999, and references therein]. They could be tested using our analytic results which enable to calculate Euler potentials and to trace magnetic field lines with high accuracy.…”
Section: Introductionmentioning
confidence: 99%